The use of the contraceptive pill and its hormonal changes in pharmacy students at a private college in the interior of Bahia (Research, Society and Development, 2022)
Oral hormonal contraceptives (ACHOs), popularly known as the contraceptive pill, have hormonal control as their main function, based on a combination of hormones. Thus, the objective of this work was to analyze the use of the contraceptive pill and its hormonal changes in pharmacy students from a private college in the interior of Bahia. The research refers to the descriptive, exploratory, qualitative and quantitative research model. To carry out this research, an online questionnaire was used in which the population was composed of university women over 18 years old who make use of contraceptives, having as place of collection a private college in the interior of Bahia, collected between the months of August and September. As a result we had that contraceptives are safe and have numerous benefits such as menstrual cycle control, acne control and minimization of cramps and blood flow. The study shows a significant reduction of university students before using the contraceptive and after using it, the blood flow from 71.4% went to 3.1% with the use of contraceptives, the deregulated cycle shows a reduction of 60.7% to 6.3%, another relevant data is referring to cramps, which show a reduction from 67.9% to 12.5%, migraine had a reduction of 17.9%, and acnes also had a reduction of 3.6% to 3.1%.